2006
DOI: 10.1073/pnas.0605086103
|View full text |Cite
|
Sign up to set email alerts
|

Basonuclins 1 and 2, whose genes share a common origin, are proteins with widely different properties and functions

Abstract: Basonuclin (bn) 1 possesses three separated pairs of zinc fingers and a nuclear localization signal. It is largely confined to the basal cells of stratified squamous epithelia and to reproductive germ cells. bn1 can shuttle between the nucleus and the cytoplasm, and its location is correlated with the proliferative potential of the cell. The recently discovered bn2 also possesses three separated pairs of zinc fingers and a nuclear localization signal. Conservation of the zinc fingers and the nuclear localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 29 publications
4
46
0
1
Order By: Relevance
“…The apparent molecular mass of insoluble BNC2 is 145 kDa (Vanhoutteghem and Djian, 2006). We also found that, in human keratinocytes, there exists a second BNC2 isoform with a molecular mass of 160 kDa and a homogenous distribution throughout the nucleus.…”
Section: In Mouse Testis Bnc2 Is Presumably a Dna-binding Protein Anmentioning
confidence: 54%
“…The apparent molecular mass of insoluble BNC2 is 145 kDa (Vanhoutteghem and Djian, 2006). We also found that, in human keratinocytes, there exists a second BNC2 isoform with a molecular mass of 160 kDa and a homogenous distribution throughout the nucleus.…”
Section: In Mouse Testis Bnc2 Is Presumably a Dna-binding Protein Anmentioning
confidence: 54%
“…19 BNC1 and BNC2 show nonoverlapping patterns of expression, and BNC2 but not BNC1 localizes to nuclear speckles, suggesting that BNC2 functions in mRNA processing. 20 Bnc2 À/À knockout mice die perinatally, with cleft palate and other craniofacial abnormalities. 21 We serendipitously identified a man with a de novo balanced 9;13 translocation and distal hypospadias, partial anomalous pulmonary venous return (PAPVR) and mild lower-limb length inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Bnc1 and bnc2 are thought to possess different functions, since bnc2 but not bnc1 localizes to nuclear speckles and therefore is likely to have a function in nuclear processing of mRNA (14).…”
mentioning
confidence: 99%